The Nexus of Water Scarcity and Climate Change: Understanding Interconnected Challenges and Formulating Resilient Strategies - Khan, Tanzim; Samiullah, Mohammed; Rouf, Istiak; Sultana, Sanjida; Rahman, Shiblur; Rahman, Bazlur; Khanum, Roufa (International Journal of Environmental Sciences, 2024)
Purpose: This research explores the intricate relationship between water scarcity and climate change, recognizing their interconnected challenges and the need for resilient strategies. Through a multifaceted approach, the study examines global impacts, socio-economic ramifications, and strategies for mitigation. Methodology: Using qualitative research methods, diverse perspectives from 40 individuals across various sectors are captured through interviews. Thematic analysis of these insights reveals the nuanced dynamics of the nexus between water scarcity and climate change. Findings: The results underscore the urgent need for comprehensive understanding and action. Rising temperatures, altered precipitation patterns, and melting glaciers exacerbate water stress, threatening ecosystems, societies, and economies globally. Socioeconomic implications include reduced agricultural productivity, compromised food security, and increased vulnerability of marginalized communities. Resilient strategies are proposed, including Integrated Water Resource Management, Climate Resilient Infrastructure, and Sustainable Agricultural Practices. Additionally, fostering Community Engagement, Policy Reform, and International Cooperation are vital. Nature-based solutions offer promise in mitigating impacts, while education and awareness-raising efforts are crucial for building resilience. Unique Contribution to Theory, Practice and Policy: This research provides a roadmap for addressing the interconnected challenges of water scarcity and climate change, emphasizing the importance of coordinated action and sustained commitment at all levels. By implementing these strategies, we can pave the way for sustainable water management and adaptation to a changing climate, ensuring the well-being of present and future generations.